2000
DOI: 10.1074/jbc.m006445200
|View full text |Cite
|
Sign up to set email alerts
|

PRMT3 Is a Distinct Member of the Protein Arginine N-Methyltransferase Family

Abstract: S-Adenosyl-L-methionine-dependent protein arginine N-methyltransferases (PRMTs) catalyze the methylation of arginine residues within a variety of proteins. At least four distinct mammalian family members have now been described, including PRMT1, PRMT3, CARM1/ PRMT4, and JBP1/PRMT5. To more fully define the physiological role of PRMT3, we characterized its unique putative zinc-finger domain and how it can affect its enzymatic activity. Here we show that PRMT3 does contain a single zinc-finger domain in its amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 40 publications
2
96
0
Order By: Relevance
“…It has been proposed that the relatively short N terminus of mammalian PRMT1 and yeast Rmt1/Hmt1 may contribute to methyltransferase substrate specificity by interacting with regions of the substrate protein distinct from the sequence immediately surrounding the target arginine residue (29,30). In addition, deletion of the relatively long unique N terminus of PRMT3 altered its substrate specificity in vitro (33). However, mutants of CARM1 lacking the unique N-or C-terminal regions appeared to be unaffected in their ability to methylate histone H3 (Fig.…”
Section: Role Of the Unique N-and C-terminal Regions Of Carm1 In Its mentioning
confidence: 96%
See 1 more Smart Citation
“…It has been proposed that the relatively short N terminus of mammalian PRMT1 and yeast Rmt1/Hmt1 may contribute to methyltransferase substrate specificity by interacting with regions of the substrate protein distinct from the sequence immediately surrounding the target arginine residue (29,30). In addition, deletion of the relatively long unique N terminus of PRMT3 altered its substrate specificity in vitro (33). However, mutants of CARM1 lacking the unique N-or C-terminal regions appeared to be unaffected in their ability to methylate histone H3 (Fig.…”
Section: Role Of the Unique N-and C-terminal Regions Of Carm1 In Its mentioning
confidence: 96%
“…However, CARM1 is the only member of the family to harbor unique domains at its N and C termini. The contribution of these additional domains to the function of the PRMTs is unknown, although some studies suggest that they may be involved in the specificity of protein substrate binding (29,30,33). Previous studies indicate that while the methyltransferase activity of CARM1 is required for coactivator function, other unspecified domains also contribute (25).…”
mentioning
confidence: 99%
“…Another unique property of PRMT3 is that it harbors a zinc finger domain at its N terminus. It has been proposed that this domain may play a role in the regulation of PRMT3 activity or in the recognition of PRMT3 substrates (6,10). Deletion analysis studies demonstrated that PRMT3 lacking the zinc finger domain is still active in vitro, however the zinc finger minus enzyme loses its ability to methylate substrates when presented with a complex mix of hypomethylated proteins isolated from RAT1 cells (10).…”
mentioning
confidence: 99%
“…Most RBPs contain GAR domains, which consist of a repetition of RGG or RXR (X is an aliphatic residue) (11,58) and are the canonical targets for type I PRMTs that catalyze the formation of asymmetric NG,NG-dimethylarginine residues (37,49). Type I enzymes PRMT1 and PRMT3 favor GAR domains as their substrates (18,25,66), and especially PRMT1 has a promiscuity to methylate arginine residues encompassed by GAR domains (65,66). On the other hand, another type I enzyme, CARM1, methylates a narrow spectrum of proteins, histone H3 (12,44), p300/CBP (69), PABP1, and TARPP (39), all of which lack GAR-like domains around the arginine residues.…”
mentioning
confidence: 99%